Analysis The Influence Of Inflation Levels and BI Rate On Baznas Zis Collection In 2005 – 2015 - Muhammad Zeinny Hasbunallah Sasmita Muhammad Zeinny; Nandu Saprudin Nandu Saprudin; Deti Kirana Deti Kirana; Harun Indra Kusuma Harun Indra Kusuma; Sofyan Sandy Sofyan Sandy; Dita Aulia Dita Aulia (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study examines the effect of inflation on the accumulation of Zakat, Infaq, and Sadaqah (ZIS) conducted by the National Zakat Agency (BAZNAS) in Indonesia from 2005 to 2015, including the effect of the BI rate and their simultaneous influence on ZIS collection. Methodology: This investigation uses a quantitative framework using time series data from BAZNAS regarding ZIS receipts and the percentage of inflation over a specified time period. The data analysis method used is Multiple Linear Regression, requiring classical assumption tests including t-tests, F-tests, multicollinearity, heteroscedasticity, and autocorrelation tests. Results: The results show a substantial relationship between inflation and ZIS accumulation, indicating that increasing inflation affects community donations for zakat. Findings: These findings emphasize the need for tactical modifications in the approach to zakat collection during periods of economic volatility. Novelty & Originality: This study provides meaningful knowledge for decision makers and BAZNAS by examining the macroeconomic determinants of ZIS collection during a ten-year period. Conclusions: The study concludes that inflation significantly influences ZIS accumulation, requiring adaptive strategies to ensure sustainable financial resources for the underprivileged. Type of Paper: This paper is an empirical research paper.